The influence of knowledge, attitude and sensitivity to government policies in halal certification process on organizational performance - Baharudin Othman; Sharifudin Md. Shaarani; Arsiah Bahron (Emerald Group Publishing Limited, 2017)
Purpose: The purpose of this research is to observe how the industry’s knowledge, attitude and sensitivity of the industry to the government’s current policy regarding the halal certification process influence the organization performance. Design/methodology/approach: This study used a self-administered questionnaire with closed-ended questions to measure the human capital factors and the practice of halal requirements. The questionnaire was distributed to multinational companies and small and medium enterprises (SMEs) in Malaysia, of which 206 responses were usable for analysis. The respondents were halal committee members in the respective companies. Smart PLS version 2.0 was used to analyze the relationship of each construct using the structural equation modeling (SEM) approach. The outcome of this study showed a positive relationship between knowledge of and attitude and sensitivity toward government policies and organizational performance. Findings: The outcome of this study showed a positive relationship between knowledge, attitude, sensitivity to government policy and organizational performance. The R2 value for the main model is 0.419, indicating that 41.9 per cent of the variance in the extent of collaboration can be explained by knowledge, attitude and sensitivity to government policies. Result also showed that all the hypotheses were supported and were significant at p < 0.01. It also showed that the control of an organization’s internal resources through human factors ranging from knowledge, attitude and sensitivity to government policies should be emphasized, as it is a contributing factor, and it strives to improve organizational performance. Research limitations/implications: There were a limited number of respondents. A larger number of respondents would reflect a more accurate study. Besides, this study only focused on the halal food industry operators, while the presence of halal now covers other schemes such as logistics, consumer products and others. Moreover, this study only focused on two main groups: multinational companies and SMEs. Practical implications: This study has provided some major implications. First, on behalf of the state, the results of this study clearly show that the human capital factor should be prioritized. Second, on behalf of the industry, this study can fill the void that exists in strengthening the industry through efforts to improve internal controls related to organizations including attending halal food courses and applying values among members of the organization. Third, the implication to theory and literature that the research-based view is suitable for use even in the food industry has been proved. Social implications: The results of this study can increase consumer confidence in the management of an organization, especially in the halal food industry. Originality/value: Halal’s rapid development has led many researchers to study halal. Till now, there is no research on three major areas of human capital aspects, namely, knowledge, attitude and sensitivity to governmental policies that involve internal halal committee members in the industry as subject of study in one model. Moreover, this research attempts to cover the latest acts, standards, procedures and guidelines provided by the government.